Kualitas Pelayanan Pengaruhnya Terhadap Kepuasan Pelanggan Transportasi Online di Kota Makassar - Mustari Mustari; Muh. Ihsan Said (Seminar Nasional LP2M UNM, 2019)
Abstract. This study aims to explain the effect of service quality on customer satisfaction on users of online transportation services. This research is a verification study with that population, all online transportation users in Makassar city and a sample of 100 online transportation users. Data collection techniques used were observation, questionnaires and documentation. The testing techniques carried out included a questionnaire test consisting of a validity and reliability test, a classic assumption test consisting of a multicollinearity test, a heteroscedasticity test, a normality test, a simple linear regression analysis, a hypothesis test consisting of a t test and a coefficient of determination. The results showed that the quality of service is categorized as